2017
DOI: 10.1155/2017/3412723
|View full text |Cite
|
Sign up to set email alerts
|

Structural Optimization Design of Large Wind Turbine Blade considering Aeroelastic Effect

Abstract: This paper presents a structural optimization design of the realistic large scale wind turbine blade. The mathematical simulations have been compared with experimental data found in the literature. All complicated loads were applied on the blade when it was working, which impacts directly on mixed vibration of the wind rotor, tower, and other components, and this vibration can dramatically affect the service life and performance of wind turbine. The optimized mathematical model of the blade was established in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In the second case, the delamination of two layers was simulated, and in the third case, the deterioration of three layers was taken into account in the finite element analysis. The delaminated surfaces were determined taking into account the risk areas presented by the blades during operation according to the literature [ 2 , 3 , 4 , 5 ].…”
Section: Modeling Of Damaged Fiberglass-reinforced Polymer Matrix Com...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the second case, the delamination of two layers was simulated, and in the third case, the deterioration of three layers was taken into account in the finite element analysis. The delaminated surfaces were determined taking into account the risk areas presented by the blades during operation according to the literature [ 2 , 3 , 4 , 5 ].…”
Section: Modeling Of Damaged Fiberglass-reinforced Polymer Matrix Com...mentioning
confidence: 99%
“…However, lighter blades also have the advantage of lighter loads at the base, as well as those on the rest of the structure, which in turn reduce the total weight and costs. The occurrence of blade damage is conditioned by the simultaneous action of factors: tensile stresses that occur due to centrifugal force and bending moments produced by wind pressure; plastic deformations that develop as a result of the stress of the material in the plastic field, correlated with the aggressive environmental factors that lead to the degradation of the elastic properties of the material; variable loads which, in the case of the blade, are due both to the variable action of the wind and the cyclic stresses that occur during the rotation of the blades by the kinetic energy of the wind, vibrations, and even resonance phenomena [ 5 , 6 , 7 , 8 , 9 ]. Research has shown that the most common types of damage are cracks; delamination; and peeling of joints, cracks, or exfoliations [ 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…This methodology combines the general optimization with robust optimization organically. Therefore, general optimization is first implemented to improve the blade performance, 20 and then, the optimal results and its robustness level are analyzed comprehensively. The evaluation results test whether robust optimization is necessary.…”
Section: Introductionmentioning
confidence: 99%